PENGARUH MEDIA TANAM DAN PUPUK ORGANIK CAIR BONGGOL PISANG (Musa sp.) TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH ( Allium cepa L.) - Mokti wibowo, Waloyo; Puspitorini, Palupi; Kurniastuti, Tri; Widiatmanta , Jeka (grafting, 2024)
Shallots are a horticultural crop that is very important for society. One effort to increase production is by providing Banana Weevil POC. This research aims to determine the effect of planting media and liquid organic fertilizer from banana weevil (Musa sp.) on the growth and yield of local varieties of shallot plants (Allium cepa L.). This research was carried out on residential land located at Bendorejo Hamlet, Bendosewu Village, Talun District, Blitar Regency. In April-June 2023. The research was prepared using (RAK) factorial with two factors, namely the composition of the planting media (M) and the concentration of Banana Weevil POC (D), with each treatment having 3 replications. Observations were made after the plants were 7 days after planting, with an observation interval of 14 days. The observation parameters include plant height, number of leaves, number of tubers, and tuber weight. The results of the research showed that the combination treatment of cow dung and Banana Weevil POC with a concentration of 10 ml had a significant effect on plant height, number of tubers and tuber weight. However, it has no effect on the number of leaves.